2019
DOI: 10.1002/14651858.cd004905.pub6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-micronutrient supplementation for women during pregnancy

Abstract: Analysis 1.12. Comparison 1 Multiple micronutrients vs control, Outcome 12 Very preterm birth (before 34 weeks of gestation).... Analysis 2.1. Comparison 2 Subgroup analysis for primary outcomes (MMN with iron and folic acid vs iron with or without folic acid)), Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
240
5
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(302 citation statements)
references
References 311 publications
10
240
5
21
Order By: Relevance
“…A recent Cochrane review reported slightly different estimates of the overall effect of MMS compared with IFA, particularly for preterm birth and stillbirth . For this analysis, we applied overall estimates from Smith et al .…”
Section: Methodsmentioning
confidence: 99%
“…A recent Cochrane review reported slightly different estimates of the overall effect of MMS compared with IFA, particularly for preterm birth and stillbirth . For this analysis, we applied overall estimates from Smith et al .…”
Section: Methodsmentioning
confidence: 99%
“…The analyses in the Cochrane Review demonstrated that overall MMS resulted in a 12% reduction in LBW (RR: 0.88; 95% CI: 0.85–0.91) and a 8% reduction in SGA births (RR: 0.92; 95% CI: 0.88–0.97), compared with IFA supplementation, with high and moderate quality evidence (based on GRADE criteria), respectively . There were no significant differences identified for other maternal or pregnancy outcomes assessed, including preterm birth, stillbirth, maternal anemia in the third trimester, miscarriage, maternal mortality, perinatal mortality, neonatal mortality, or risk of delivery by caesarean section when MMS was compared with supplementation with iron or without folic acid.…”
Section: Revisiting the Evidence Base On The Effect Of Multiple‐micromentioning
confidence: 96%
“…There were no significant differences identified for other maternal or pregnancy outcomes assessed, including preterm birth, stillbirth, maternal anemia in the third trimester, miscarriage, maternal mortality, perinatal mortality, neonatal mortality, or risk of delivery by caesarean section when MMS was compared with supplementation with iron or without folic acid. A summary of these analyses is presented in Table , alongside the results from the IPD meta‐analysis for comparison, which is discussed in more detail below . However, it should be noted that the IPD was based on voluntary participation of the trial's investigators and was primarily aimed at conducting subgroup analyses, while the Cochrane Review was focused on the overall effects of all available trials.…”
Section: Revisiting the Evidence Base On The Effect Of Multiple‐micromentioning
confidence: 99%
“…In comparison to current recommendations, there is some variation in the UNIMMAP formulation around 100% of the RDA/AI; however, all values are substantially below ULs. As well, more than 20 randomized controlled trials have been published comparing multiple micronutrient (often, but not always similar to UNIMMAP) to iron and folic acid supplementation in LMIC . Conducting such trials is inherently challenging, and morbidities such as nausea and vomiting were either not collected or have not yet been reported in a way that would allow collective conclusions about the side effects of supplementation …”
Section: Potential For Excess Intake When Taking Daily Unimmapmentioning
confidence: 99%